TCF-1-Centered Transcriptional Network Drives an Effector versus Exhausted CD8 T Cell-Fate Decision - Chen, Zeyu; Ji, Zhicheng; Ngiow, Shin Foong; Manne, Sasikanth; Cai, Zhangying; Huang, Alexander C; Johnson, John; Staupe, Ryan P; Bengsch, Bertram; Xu, Caiyue; Yu, Sixiang; Kurachi, Makoto; et al. (Immunity (Cambridge, Mass.), 2019)
TCF-1 is a key transcription factor in progenitor exhausted CD8 T cells (Tex). Moreover, this Tex cell subset mediates responses to PD-1 checkpoint pathway blockade. However, the role of the transcription factor TCF-1 in early fate decisions and initial generation of Tex cells is unclear. Single-cell RNA sequencing (scRNA-seq) and lineage tracing identified a TCF-1 Ly108 PD-1 CD8 T cell population that seeds development of mature Tex cells early during chronic infection. TCF-1 mediated the bifurcation between divergent fates, repressing development of terminal KLRG1 effectors while fostering KLRG1 Tex precursor cells, and PD-1 stabilized this TCF-1 Tex precursor cell pool. TCF-1 mediated a T-bet-to-Eomes transcription factor transition in Tex precursors by promoting Eomes expression and drove c-Myb expression that controlled Bcl-2 and survival. These data define a role for TCF-1 in early-fate-bifurcation-driving Tex precursor cells and also identify PD-1 as a protector of this early TCF-1 subset.